STRATEGI GURU DALAM MEMBENTUK LINGKUNGAN BELAJAR YANG INKLUSIF - Yolanda Pattinasarany; Margarita Seleky; Henlis Tomhisa; Fanesya Tasidjawa (Yayasan Nusantara Hasana Berdikari, 2025)
The value of inclusive classrooms where all students have equal opportunities to learn and develop, regardless of their background or special needs. This publication presents the methods educators use to ensure inclusion in the classroom, such as curriculum adaptation, learning differentiation, and the application of social-emotional learning techniques. According to research, teachers can foster a learning environment that values ​​diversity, increases student engagement, and ensures that every student has an equitable educational experience by implementing the right tactics.